Modern industry and the African : an enquiry into the effect of the copper mines of Central Africa upon native society and the work of the Christian missions /: an enquiry into the effect of the copper mines of Central Africa upon native society and the work of the Christian missions. (2018) - Davis, J. Merle (John Merle), 1875-1960
No abstract available